PENGARUH BERBAGAI MACAM WARNA PENCAHAYAAN TERHADAP PERFORMA AYAM PEJANTAN PADA FASE GROWER: THE EFFECT OF VARIOUS LIGHTING COLORS ON THE PERFORMANCE OF MALE CHICKEN IN THE GROWER PHASE - Mahendra, Gilang Wisnu; Wulandari, Eudia Christina; Abdurrahman, Zakaria Husein (Universitas Boyolali, 2023)
The male chicken is the result of laying hens that are male, therefore it is called a male. Broilers are usually harvested when they are two or three months old. In terms of structure, roosters are usually smaller than other types of chickens and have a pure white color. Laying hens of the male type are a by-product of the production of breeding and hatching of laying hens. Laying cocks are considered to have the ability to produce meat. The lighting program is one that is very influential in achieving peak production in relation to uniformity of sexual maturity. The purpose of feeding in the grower phase is to encourage or stimulate the chickens to grow faster, not just grow. So that the development of hereditary organs becomes optimal and supports further sustainable growth.